PIBID Dança: Building relationships in/with dance in the school environment - Oliveira, Isabella Moreira de (2023)
This article focuses on the analysis of the relationships developed by the Institutional Scholarship Program for Teaching Initiation (PIBID) in the area of ​​dance knowledge in the school environment. In this context, we discuss about the artistic experiences provided by the program, in addition to contextualizing these experiences with observations and notes in dialogue with the theoretical contributions of references on dance in the school context, such as Isabel Marques (2010) and Márcia Strazzacappa and Carla Morandi (2012). Given the above, methodologically supported by the experience report, this article describes the pathways, challenges and knowledge gathered in the work of professionals in teacher training, supervisors and students, as well as the reception and involvement of other members of the school community.